THE ROLE OF GROUP A BETA-HEMOLYTIC STREPTOCOCCUS INFECTION IN THE PATHOGENESIS OF RHEUMATIC HEART DISEASE: A SYSTEMATIC LITERATURE REVIEW - Zelia Maria da Silva; Jubilia A. B. dos Reis Belo (Jurnal Kesehatan Karya Husada, 2025)
Introduction Group A β-hemolytic Streptococcus (Streptococcus pyogenes) infection is the main cause of various infectious diseases in humans, including rheumatic fever and rheumatic heart disease. Rheumatic fever is an inflammatory disease that arises as a response to streptococcal infection, with serious complications in the form of heart valve damage. Although it can be treated with antibiotics, delayed treatment or repeated infections can cause permanent heart damage. This study aims to examine the role of Streptococcus pyogenes in the pathogenesis of rheumatic heart fever through a systematic literature review. Methods This study used a systematic literature review method to analyze relevant scientific articles on Streptococcus pyogenes, rheumatic fever, and rheumatic heart disease. Literature sources were taken from leading databases, such as Scopus and PubMed. The search process was conducted using keywords related to streptococcal infection, rheumatic fever, and the pathogenesis of heart disease. Results The results of the study indicate that Streptococcus pyogenes plays an important role in the pathogenesis of rheumatic heart fever through various mechanisms, such as immune evasion and the influence of environmental and genetic factors. Repeated infection with certain strains of Streptococcus pyogenes, such as M1T1, can exacerbate the body's immune response and worsen damage to the heart valves. The study also highlights the role of vaccination and antibiotic use in preventing streptococcal infections and heart complications. Discussion. This study reveals that immune evasion by Streptococcus pyogenes plays a major role in the development of autoimmunity that causes heart damage. Repeated infection with virulent strains such as M1T1 has the potential to increase the severity of rheumatic heart disease. Preventive approaches through timely administration of antibiotics and vaccine development have great potential in reducing the prevalence of this disease. However, challenges such as antibiotic resistance and co-infection with viruses still require further attention. Keywords: Streptococcus pyogenes, rheumatic fever, rheumatic heart disease, pathogenesis, recurrent infection, immunopathology, antibiotics, vaccination